Rethinking the School of Chartres - Jeauneau, Édouard, 1924-2019 (Rethinking the Middle Ages, 2009)
In this brief essay, esteemed medieval historian Edouard Jeauneau examines a much-debated question in medieval intellectual history: did the famous School of Chartres actually exist? Gracefully acknowledging the suggestion by Sir Richard Southern in 1965 that the School was actually a myth, Jeauneau argues that the School did in fact exist but perhaps was not as important as previously thought. Jeauneau provides a fascinating portrait of the School of Chartres during its heyday in the first half of the twelfth century, bringing to light the accomplishments of Fulbert of Chartres, Bernard of Chartres, Thierry of Chartres, Gilbert of Poitiers and William of Conches. Deftly translated by Claude Paul Desmarais, Rethinking the School of Chartres provides a narrative that is critical, passionate, and witty. Sixteen black-and-white images are included. This is the third title in a series called Rethinking the Middle Ages, which is committed to re-examining the Middle Ages, its themes, institutions, people, and events with short studies that will provoke discussion among students and medievalists, and invite them to think about the middle ages in new and unusual ways. The series editor, Paul Edward Dutton, invites suggestions and submissions.